Comparative Study on Conductance Measurements At 25oC of Ionic Association of Acetylcholine and S-Acetylthiocholine Bromides in Aqueous and Non-Aqueous Solvents - NASR H. EL-HAMMAMY,; AIDA I. KAWANA,; MOUSTAFA M. EL-KHOLY, (International Journal of Pharma and Bio Sciences, 2010)
Conductance measurements of ion-pair association of acetylcholine and s- acetylthiocholine bromides in aqueous and non-aqueous solvents at 25°C were found to depend on the association of the cation and increased with increasing cation crystallographic radius. Solvation of cation increased with increasing cationic size in aqueous and non-aqueous solvents.The association constant KA was analyzed on the basis of solvent separated- ion pair model.